BS EN IEC 55016-4-6. Specification for radio disturbance and immunity Measuring apparatus and methods. Part 4-6. Uncertainties, statistics and limit modelling. Statistics on radio frequency interference (RFI) and verification by measurements in the field (13th August 2021) - British Standards Institution,
No abstract available